Endothelial cell-derived extracellular vesicles exert cardio-protective effect via their protein cargo. (25th November 2020) - Ravera, F; Femmino', S; Penna, C; Franchin, L; Angelini, F; Tapparo, M; Lopatina, T; Espolin Fladmark, K; Alloatti, G; Camussi, G; D'Ascenzo, F; Pagliaro, P; et al.
Abstract: Background: Extracellular vesicles (EV) are recognized as carriers of relevant biological effects and have been identified as regulators of cell-to-cell communication contributing to several patho-physiological processes. These processes include angiogenesis/coagulation/tissue repair/inflammation. In ischemia/reperfusion (I/R) settings, along with the direct effects of the I/R itself, paracrine mechanisms associated with the activation of the inflammatory response, primary involving endothelial cells, are crucial drivers of both vessel and cardiomyocyte damage. Purpose: Since in models of myocardial I/R injury the role of EV released from endothelial cells is still unclear, our hypothesis was to provide insight on this specific topic. To this end, naïve endothelial cell (EC)-derived EV (eEV) and eEV released in response to the pro-inflammatory cytokine interleukin-3 (IL-3) (eEV-IL-3) have been evaluated on different I/R models. Methods: eEV were characterized by MACSPlex-Exosome-Kit and western blot analysis. For the in-vitro hypoxia-reoxygenation (H/R) experiments, H9c2 or EC were pretreated with eEV, eEV-IL-3 (1x104 EV/cell) or IL-3 (10ng/ml) for 2 hours and then exposed to hypoxia (1% O2, 5% CO2) for additional 2 hours in the presence of eEV, eEV-IL-3 or IL-3 and subsequently reoxygenated (21% O2 and 5% CO2) for 1 hour. To verify the effect of EC treated with eEV, eEV-IL-3 or IL-3 on H9c2 and subjected to H/R protocol, transwell assay was used. At the end of the H/R protocol, cell viability was assessed. For ex-vivo experiments, isolated rat hearts, pretreated with a buffer containing EV (from EC pretreated or not with IL-3), were subjected to 30 minutes global normothermic ischemia and 1 hour reperfusion. Triton infusion was also used as a model of endothelial damage. At the end of I/R, the infarct size was measured and expressed as a percentage of total left ventricular mass (LVM). The role of eNOS/guanylyl-cyclase/MEK1/2 pathways in mediating eEV biological effects was also evaluated using different inhibitors both in in-vitro and ex-vivo models. Finally, protein profiles of eEV and eEV-IL-3 were analyzed using label free mass spectrometry. Results: eEV and eEV-IL-3 protect EC, but not H9c2 exposed to H/R protocol, while eEV, but not eEV-IL-3-treatment limits I/R injury in the rat heart. Rat hearts pre-treated with triton significantly avoid eEV-induced cardio-protection. Transwell assay showed a reduction of H9C2 mortality after treatment with both eEV and eEV-IL-3. Proteomic analysis revealed that MEK1/2 and the endothelial-NOS (eNOS)-antagonist caveolin-1 were differentially expressed in eEV and eEV-IL-3. The use of eNOS/guanylyl-cyclase/MEK1/2 inhibitors prevented eEV-induced cardio-protection. Conclusions: These observations indicate that eEV, but not eEV-IL-3, have cardio-protective effects when given as preconditioning agents. We have also shown that the activation of eNOS/GC/MEK1/2 pathway is crucial for eEV-mediated cardio-protection. Funding Acknowledgement: Type of funding source: None